SYNTHESIS AND PHOTOCHEMICAL PROPERTIES OF NEW STYRYLQUINOLINE-CONTAINING POLYMERS - Kharchenko, Oksana; Smokal, Vitalii; Kolendo, Oleksii (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2022)
Compounds 1a, 1b and 5c, 5d were obtained by Knoevenagel condensation with the corresponding aromatic aldehydes during 14 hours. The new methacrylic monomers with styrylquinoline containing moiety were synthesized by reaction the alcohols with methacryloyl chloride. Polymers were synthesized by free radical polymerization. Polymerization ability was investigated and kinetic parameters were determined for compounds 2a, 2b and 6c, 6d during thermoinitiated homopolymerization. Polymerization was carried out for 10% solutions of monomers in DMF at 80 °C in argon atmosphere with 1% AIBN. Polymers were characterized by 1HNMR spectroscopy. The speed of polymerization of all new monomers was higher than for MMA and phenyl methacrylate due to the effect of the substituent in the p-position of the aromatic ring of the styrylquinoline fragment. In addition, the speed of polymerization increased due to the donor effect of the substituent. It was established that the speed of polymerization for 2b is higher than for monomer 2a. It is possible that decrease in the speed of polymerization occurs due to the substituent, which exhibits electron-accepting properties and can be a trap for free radicals. The results of photochemical and optical activities of the corresponding polymers are presented. Investigations of the absorption spectra of the synthesized polymers prove that the optically active styrylquinoline fragment in the polymers is preserved. Thus the photochemical properties of the new polymers will correspond to the properties of styrylquinoline-containing compounds. It was established that the introduction of electron-donating groups in the styrylquinoline fragment leads to a bathochromic shift of the absorption spectrum. Changes in absorption maxima during UV irradiation of compound 3a demonstrate photoinduced trans-cis isomerization. From the obtained and presented results, it can be concluded that polymers with styrylquinoline and iminostyrylquinoline fragments can be considered as promising materials for creating materials based on them that require photosensitivity in a certain range of wavelengths.